Safety and efficacy of Biomin® DC‐P as a zootechnical feed additive for chickens for fattening, chickens reared for laying and minor avian species to the point of lay. (11th June 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The additive (trade name Biomin ® DC‐P) is a blend of five individual compounds (carvacrol, thymol, d ‐carvone, methyl salicylate and l ‐menthol) encapsulated with a hydrogenated vegetable oil. The additive is intended for use in feed for various poultry species at a minimum concentration of 65 mg/kg complete feed and a recommended maximum level of 105 mg/kg complete feed. The results of a tolerance study show that Biomin ® DC‐P is safe for chickens for fattening at the maximum recommended application rate of 105 mg/kg complete feed; this conclusion is extended to include chickens reared for laying and extrapolated to minor poultry species The active components of a previously evaluated additive (Biomin ® DC‐C) were shown to be not genotoxic; owing to the similarity on composition, this conclusion can be also applied to Biomin ® DC‐P. Notwithstanding the uncertainties identified in the residue study, after applying a worst‐case scenario to calculate potential exposure of consumers to menthol and carvone, and since that the components of the additive are considered safe for their use as food and feed flavourings, the FEEDAP Panel concludes that the use of the additive in animal nutrition is considered safe for consumers. The FEEDAP Panel considered that exposure of users by inhalation is unlikely, but cannot conclude on the effects of Biomin ® DC‐P on skin and eyes. The use of Biomin ® DC‐P is not expected to pose a risk for the environment. Biomin ® DC‐P has a potential to increase the growth performance of chickens for fattening when incorporated into feed at a minimum application rate of 65 mg/kg complete feed; the conclusion can be extended to chickens reared for laying and extrapolated to minor poultry species reared up to the point of lay.